Implementation Of The School Health Program (UKS) In Improving Clean And Healthy Living Behavior (PHBS) : A Qualitative Study At SMPN 6 Singosari - Selvia Redita Dwi Ruhisaadah; Wandi; Tavip Dwi Wahyuni; Jupriyono (Poltekkes Kemenkes Semarang, 2026)
The UKS program is closely linked to the promotion of PHBS, but its suboptimal implementation often hinders the improvement of PHBS in schools. The purpose of this study was to determine the implementation of the UKS program in improving PHBS at SMPN 6 Singosari. The research method used was qualitative with a case study approach. Data collection techniques through in-depth interviews, FGDs, observation, and documentation. Informants consisted of 4 interview informants and 8 FGD informants. The results of this study indicate that health education has been integrated into the curriculum; health services are provided internally and externally; and the healthy school environment program has focused on sanitation, land use, disease prevention, and ensuring schools are free from smoking, drugs, and bullying; PHBS at SMPN 6 Singosari has not yet met the 8 PHBS indicators in schools; Supporting factors include the availability of a UKS room, collaboration with the Singosari Community Health Center, and active mentors. Inhibiting factors include limited funding, the quantity and quality of human resources, and student non-compliance with UKS regulations. Recommendations include establishing and developing school health cadres, integrating health education into routine Friday programs, optimizing health promotion media, and collecting data on health infrastructure.